Japan in the United States Reverse Course: An Inter-imperial Analysis of Kazuo Ishiguro’s An Artist of the Floating World - Hui Chien, Ngoi (SARE: Southeast Asian Review of English, 2025)
This article examines how Kazuo Ishiguro’s An Artist of the Floating World (1986) represents the ambivalence of Ono, its Japanese narrator in postwar Japan, as he confronts his past role in creating propagandistic posters for the Japanese Empire’s militarism during the United States Reverse Course. After World War II, the US occupation of Japan (1945–1952), which marked the US Empire’s dismantling of the Japanese Empire, initially sought to demilitarise Japan. However, to counter communism, around 1947 or 1948, the US introduced the Reverse Course in Japan, which contradictorily relaxed its demilitarisation efforts and permitted remilitarisation. The Reverse Course’s contradictory messages about militarisation, this article argues, serve as the backdrop for Artist’s depiction of Ono’s ambivalence about his past involvement in Japanese militarism. Mobilising Laura Doyle’s inter-imperiality, the textual analysis demonstrates that, under the US Empire’s Reverse Course, Ono is ambivalent about admitting his past advocacy of the Japanese Empire’s militarism was wrong, despite acknowledging the ideology’s severe consequences in postwar Japan. It shows how the US Reverse Course perpetuated remnants of Japanese militarism after the war The findings fill the research gap of current scholarship on Artist, which is rarely grounded in Japan’s postwar history intertwined with the US.